2022
DOI: 10.1016/j.clnu.2021.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional parameters associated with prognosis in non-critically ill hospitalized COVID-19 patients: The NUTRI-COVID19 study

Abstract: Background & Aims To investigate the association between the parameters used in nutritional screening assessment (body mass index [BMI], unintentional weight loss [WL] and reduced food intake) and clinical outcomes in non-critically ill, hospitalized coronavirus disease 2019 (COVID-19) patients. Methods This was a prospective multicenter real-life study carried out during the first pandemic wave in 11 Italian Hospitals. In total, 1391 patients were included. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The nutritional consequences of COVID- 19 are not yet fully understood, but the knowledge from severely ill patients with acute respiratory distress syndrome suggests that patients are likely to experience the adverse effects of the loss of muscle mass and skeletal muscle dysfunction for weeks to years. The knowledge from a range of disease states and chronic conditions illustrates that low muscle mass is associated with higher rates of infections, poorer tolerance to chemotherapy, hospitalisation, fractures, reduced quality of life and reduced survival, with implications for patient outcomes and healthcare utilisation [15].…”
Section: Focus On Thementioning
confidence: 99%
See 3 more Smart Citations
“…The nutritional consequences of COVID- 19 are not yet fully understood, but the knowledge from severely ill patients with acute respiratory distress syndrome suggests that patients are likely to experience the adverse effects of the loss of muscle mass and skeletal muscle dysfunction for weeks to years. The knowledge from a range of disease states and chronic conditions illustrates that low muscle mass is associated with higher rates of infections, poorer tolerance to chemotherapy, hospitalisation, fractures, reduced quality of life and reduced survival, with implications for patient outcomes and healthcare utilisation [15].…”
Section: Focus On Thementioning
confidence: 99%
“…Obesity may mask malnutrition and muscle loss, but body composition, as assessed by computed tomography, confirms the loss of lean body mass in obese ICU COVID-19 patients, which could lead to the development of sarcopenic obesity [18]. In a recent study of non-critically ill hospitalised COVID-19 patients, obesity (body mass Index (BMI) ≥ 30 kg/m 2 ) in combination with two or more comorbidities were associated with increased in-hospital mortality, whereas the presence of obesity with less than two comorbidities appeared to be a protective prognostic factor [19].…”
Section: Focus On Thementioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the mechanism explaining this association is driven by insulin resistance and increased circulating inflammatory cytokines [17]. It has not been shown that weight loss reduces anxiety; on the contrary, reduced food intake prior to hospitalization has been identified as a predictor of poor outcomes in patients admitted with COVID; moreover, obesity was found to be protective against in-hospital mortality among people without comorbidities [18].…”
Section: Covidmentioning
confidence: 99%